Evaluative Study of Lecturer Competence in the Department of XYZ in Insitut Agama Kristen Negeri Tarutung - Tobing, Lasmaria Lumban; Manullang, Tetti; Gaol, Idola H. Lumban; Simanjuntak, Maria Kristina; Simamora, Roswel Mika (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
As providers of educational services, lecturers play a crucial role in tertiary institutions' operations. If lecturers possess legal competencies, tertiary institutions can perform well. This study aims to map the competence of lecturers in the XYZ study program, identify obstacles to developing lecturers' competence, and then offer suggestions for improving lecturers' competence. This study utilizes successive logical blended techniques (blend strategies consecutive illustrative). 72 students who were taught by lecturers (subjects) participated in the survey. Subjects, specifically three XYZ concentrate on program speakers, were then led to top-to-bottom meetings to have the option to recognize hindrances in the advancement of teacher abilities. The review and interview results were broken down to acquire research information. The consequences of the review show that the planning of speaker capabilities in the XYZ Study Program shows that the typical teacher skill is 67.07 where this worth is in the medium class. competence in education, with an average score of 59.92. Competence in the workplace, with an average score of 63.17. With an average score of 62.01, social competence is 61.07 social competence This leads us to the conclusion that, out of the four competencies, professional competence has the highest average, and pedagogical competence has the lowest average. Speakers face different impediments in creating academic, expert, character, and social abilities. These different deterrents come from inside the teachers, understudies, and the foundation.